1999
DOI: 10.4269/ajtmh.1999.61.180
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of viral replication and up-regulation of cytokine levels by antimalarials: implications in malaria-endemic areas.

Abstract: Abstract. Antimalarial drugs are widely used in malaria endemic areas, both for chemoprophylaxis and also empirically to treat patients presenting with fever. Previously, we have reported that chloroquine enhances the severity of Semliki forest virus (SFV) and encephalomyocarditis virus infection. The studies presented herein show that a broad spectrum of antimalarial drugs augmented the replication of SFV in mice, concomitant with greater tissue damage and up-regulation of mRNA levels of various inflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 24 publications
0
18
0
1
Order By: Relevance
“…Data of chloroquine against chikungunya virus is even more intriguing. While chloroquine had satisfactory antiviral activity against chikungunya in vitro, animal studies showed increase in virus replication, aggravation of fever and incomplete viral clearance [34]. Human trials of chloroquine showed no improvement in chikungunya acute illness and rather an increase in chronic arthralgia was observed during post-illness period, compared to the controls [35].…”
Section: Discussionmentioning
confidence: 96%
“…Data of chloroquine against chikungunya virus is even more intriguing. While chloroquine had satisfactory antiviral activity against chikungunya in vitro, animal studies showed increase in virus replication, aggravation of fever and incomplete viral clearance [34]. Human trials of chloroquine showed no improvement in chikungunya acute illness and rather an increase in chronic arthralgia was observed during post-illness period, compared to the controls [35].…”
Section: Discussionmentioning
confidence: 96%
“…The time to SARS-CoV-2 negativity test was significantly longer in patients who received HCQ compared to those who did not receive the treatment (17 [13][14][15][16][17][18][19][20][21] vs. 10 [4][5][6][7][8][9][10][11][12][13] days, p=0.023, Figure 1). The time to negativity test was not significantly different between patients with symptoms and without symptoms (14 [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] vs. 15 [4][5][6][7][8][9][10][11][12][13][14][15][16][17]…”
Section: Factors Associated With Time To Negativity Testmentioning
confidence: 99%
“…Chloroquine (10–25 μM) has been shown to confer a weak anti-HIV activity outside the range of physiological concentrations by disrupting the glycosylation of gp120 (Rayne et al, 2004; Naarding et al, 2007). None the less, some reports have demonstrated no beneficial effect of chloroquine and instead have shown increased HIV infection in vitro and a more severe form of disease outcome in brain with upregulation of viral replication of other neurotropic viruses (Kamya et al, 2001; Seth et al, 1999). Given their high endocytic activity for HIV particles (Clarke et al, 2006; Deiva et al, 2006), in the present study we investigated the impact of chloroquine on HIV infection in neuro-glial cells.…”
Section: Introductionmentioning
confidence: 99%